Performance analysis of LiAl0.5Co0.5O2 nanosheets for intermediate-temperature fuel cells. (29th July 2021) - Paydar, Sara; Peng, Jin; Huang, Liwen; Shi, Quan; Akbar, Nabeela; Islam, Quazi Arif; Muhammad, Akbar; Xing, Yueming; Kim, Jung-Sik; Wu, Yan
Abstract: Exploring high conductive materials is still a challenge for high performance intermediate-temperature fuel cells. In this study, two-dimensional LiAl0.5 Co0.5 O2 (LACO) nanosheets coated by a compatible amorphous LiAlO2 (LAO) layer are evaluated as proton/Li + conductor electrolyte. The fuel cell in which the LAO-LACO is used as electrolyte could deliver the maximum power output of 1120 mW cm −2 at 550 °C. The LAO coating enhances not only the ionic conductivity by modifying the space-charge regions, but also improves the LACO's chemical stability and device performance. Kelvin probe force microscopy further detected a local electric field (LEF) built in the LAO-LACO coating confines protons at the interface to transport fast. Such heterostructure with the LEF accelerating mechanism presents a novel approach for developing high-performance intermediate-temperature fuel cells. Highlights: LACO nanosheets coated by LAO was developed as the functional electrolyte for PCFCs. Fuel cell based on LACO modified by LAO achieves a maximum performance of 1120 mW cm −2 at 550 °C. A local electric field (LEF) built in the LACO modified by LAO exhibits a H+/Li + ionconductance at the interface.